Efeito da rochagem no crescimento e nutrição de plantas de batata - Moreira, Diulie Talita (Universidade Federal de São Carlos, 2016)
Brazil is considered a country with extreme potential for agricultural production, but with great dependence on fertilizer imports. The Brazilian area with the potato crop is estimated at 130,000 ha. It is a high nutrient-demanding crop that consumes about 1.5 t of fertilizers per ha. An alternative to increase potato quality and productivity and make the production system more sustainable is the application of stonemeal. This study aimed to evaluate the growth and productivity parameters of the potato, Ágata variety, grown under different sources and increasing doses of rock powder. The experiment was carried out under greenhouse conditions, adopting a completely randomized design, with a 5x3 factorial scheme and five replications. The first factor consisted of three different sources of rock powder [mica-schist; blend I (kamafugite + mica-schist); blend II (kamafugite + mica; schist + microorganism source (Amino Peixe Raízes®)]. The second factor was made up of the following doses: 0, 3,000, 4,000, 5,000, 6000 kg ha-1. At the end of the cycle (95 days after planting), the following parameters were analyzed: height and number of stems, number and weight of tubers and productivity. Number of stems per plant did not respond to the application of crushed rocks.The treatment with blend II provided a significant increase in the weight and number of tubers in addition to increasing productivity by 36%. The biological component added in the blend II treatment was determinant in accelerating the availability of rock nutrients during the potato cycle.
Effect of stonemeal on the growth and nutrition of potato plants
Keywords: Solanum tuberosum; Micaxisto; Kamafugito; Amino Peixe Raízes®; Pó de rocha; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO